A numerical method to determine the waiting time and the idle time distributions of a GI/G/1 queue when inter-arrival times and/or service times have geometric tails. Issue 2 (3rd April 2019) - Grassmann, Winfried K.; Tavakoli, Javad
Abstract: We discuss a numerical method to find the distributions of the waiting time and the idle time for discrete-time G I / G / 1 queueing systems when inter-arrival or service time distributions have geometric tails. We showed by numerical experiments that our algorithm converges rapidly, and that the execution times for practical problems are negligible.